1990
DOI: 10.2307/1591274
|View full text |Cite
|
Sign up to set email alerts
|

Intracloacal Salmonella typhimurium Infection of Broiler Chickens: Reduction of Colonization with Anaerobic Organisms and Dietary Lactose

Abstract: The combined effect of treatments with dietary lactose plus anaerobic organisms on cecal colonization of broiler chicks by Salmonella typhimurium was evaluated. Chickens treated with a combination of anaerobic organisms and 7% dietary lactose were resistant to cecal colonization by S. typhimurium. The number of recoverable S. typhimurium cells per gram of cecal contents taken on days 10 and 15 after infection was significantly reduced. Treatment with anaerobes without the addition of lactose did not effectivel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0

Year Published

1997
1997
2009
2009

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(24 citation statements)
references
References 7 publications
1
23
0
Order By: Relevance
“…A ST chicken isolate strain (National Veterinary Services Laboratory accession number 87-26254) previously selected for resistance to novobiocin and naladixic acid by Ziprin et al (1990) was used in this study. Maintenance and confirmation of bacterial culture integrity was described previously (Ricke et al 1988).…”
Section: Bacterial Strain and Media Preparationmentioning
confidence: 99%
“…A ST chicken isolate strain (National Veterinary Services Laboratory accession number 87-26254) previously selected for resistance to novobiocin and naladixic acid by Ziprin et al (1990) was used in this study. Maintenance and confirmation of bacterial culture integrity was described previously (Ricke et al 1988).…”
Section: Bacterial Strain and Media Preparationmentioning
confidence: 99%
“…A primary poultry isolate of Salmonella typhimurium selected for resistance (Ziprin et al 1990) to novobiocin (NO) and nalidixic acid ( (Bryant, 1972) was used for all culture manipulations and nitrogen was the head gas.…”
Section: Organisms and Culture Mediummentioning
confidence: 99%
“…Correlation studies have indicated that volatile fatty acids, particularly propionic acid, might be important in the reduction of Salmonella viable counts (19,32). However, it is not known whether the relationship between volatile fatty acids and reduction in numbers of salmonellae is causal or coincidental.…”
mentioning
confidence: 99%